1998
DOI: 10.1093/humrep/13.5.1188
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic septum resection in patients with recurrent abortions or infertility

Abstract: Fifty-seven patients who underwent hysteroscopic septum resection between January 1991 and December 1996 were studied; nine patients presented with recurrent abortions, 46 with infertility (26 primary and 20 secondary), one with dysmenorrhoea and one with an asymptomatic complete septum. Their reproductive history included 78 pregnancies: 69 (88.4%) abortions, two (2.6%) ectopics, two (2.6%) preterm deliveries and five (6.4%) term deliveries. In patients with infertility, the incidence of unexplained infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 31 publications
5
97
1
16
Order By: Relevance
“…Hysteroscopic metroplasty in this group is applied mainly as a prophylactic procedure to prevent spontaneous abortions and complications during labour [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hysteroscopic metroplasty in this group is applied mainly as a prophylactic procedure to prevent spontaneous abortions and complications during labour [3].…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızda sekonder infertil grupta septum eksizyonu öncesi düşük, preterm doğum ve canlı doğum oranları, sırasıyla, %64 (20/31), %35 (11/31) ve %3 (1/31) iken septum eksizyonu sonrasında sırasıyla, %22 (7/31), %9 (3/31) ve %45 (14/31) olarak bulunmuştur. Histeroskopik septum eksizyonu sonrası fertilite oranlarını bildiren pek çok çalışmada işlem sonrası yardımcı üreme teknikleri kullanılmıştır (13,14). Çalışmamızdaki gebelik oranları değerlendirilirken bu çalışmanın ana sonlanım öl-çütlerinin sadece spontan klinik gebelik ve sonucunda oluşan canlı doğum oranları olduğu hesaba katılmalı-dır.…”
Section: Discussionunclassified
“…A good surgical correction by metroplasty provides an anatomically normal uterine cavity, but does not unfailingly result in a favourable reproductive outcome since uterine vascularization is probably involved in the uterine function. The theory which is nowadays widely accepted states that septum consists of fibroelastic tissue with inadequate vascularization and a changed ratio between blood vessels of the endometrium and myometrium, presenting negative effects on decidualisation and placentation [14].…”
Section: Figure 1 -Schematic Presentation Of Afs Classificationmentioning
confidence: 99%
“…Hysteroscopic metroplasty has all the benefits of a good operative treatment: decreesed intra-and post-operative morbidity, shorttime intervention, fewer analgesic requirements, a shorter hospital stay, a shorter interval to conception and the possibility of a vaginal delivery. Most research findings have revealed that the majority of uterine malformations (> 55%) are presented with septate and arcuate uterus (type s5 and 6 according to AFS classification), which can be effectively treated by means of operative hysteroscopy [14,15]. Partial reconstruction of the uterine cavity by hysteroscopy is possible in some cases of partial bicornuate uterus (type 4b).…”
Section: Figure 1 -Schematic Presentation Of Afs Classificationmentioning
confidence: 99%